Two new isomeric zinc(II) metal–organic frameworks based on 1, 5‐bis(2‐methyl‐1H‐imidazol‐1‐yl)pentane and 5‐methylisophthalate ligands. Issue 2 (16th January 2017) - Tan, Xiong-Wen; Li, Heng-Feng; Li, Chang-Hong
Abstract : Two‐ and three‐dimensional zinc metal–organic frameworks (MOFs) constructed from 1, 5‐bis(2‐methyl‐1 H ‐imidazol‐1‐yl)pentane and 5‐methylisophthalic acid are reported. Both complexes show high stability and good fluorescence in the solid state at room temperature. Abstract : Many factors, such as temperature, solvent, the central metal atom and the type of coligands, may affect the nature of metal–organic frameworks (MOFs) and the framework formation in the self‐assembly process, which results in the complexity of these compounds and the uncertainty of their structures. Two new isomeric Zn II metal–organic frameworks (MOFs) based on mixed ligands, namely, poly[[μ‐1, 5‐bis(2‐methyl‐1 H ‐imidazol‐1‐yl)pentane‐κ 2 N 3 : N 3′ ](μ‐5‐methylisophthalato‐κ 2 O 1 : O 3 )zinc(II)], [Zn(C9 H6 O4 )(C13 H20 N4 )] n, (I), and poly[[μ‐1, 5‐bis(2‐methyl‐1 H ‐imidazol‐1‐yl)pentane‐κ 2 N 3 : N 3′ ](μ3 ‐5‐methylisophthalato‐κ 3 O 1 : O 1′ : O 3 )(μ3 ‐5‐methylisophthalato‐κ 4 O 1 : O 1′ : O 3, O 3′ )dizinc(II)], [Zn2 (C9 H6 O4 )2 (C13 H20 N4 )] n, (II), have been synthesized under hydrothermal conditions and characterized by single‐crystal X‐ray diffraction, IR spectroscopy, elemental analysis and thermogravimetric analysis. Complex (I) displays a two‐dimensional layer net, while complex (II) exhibits a twofold interpenetrating three‐dimensional framework. Both complexes show high stability and good fluorescence in the solid state at room temperature.